Effectiveness of two trapping protocols for studying the demography of common voles - Jánová, E. (Eva); Nesvadbová, J. (Jiřina); Heroldová, M. (Marta); Bryja, J. (Josef) (2010)
The sampling methods affect significantly the results of any study focused on demography of model species. The common vole is one of the most numerous pest species in the Czech Republic. Its populations in central Europe have been usually sampled by snap traps and/or by metallic single-capture live traps type "Rödl". Furthermore, different baits were used which could cause significant bias in collected data. In this study, we simultaneously captured the population of common vole (Microtus arvalis) using both methods and we compared body size, age, sex ratio and proportion of reproductively active females in gained samples. Age structure was biased toward older individuals in live traps, though the difference in body size was not found. There was higher proportion of reproductively active females and sex ratio was female biased in live traps. These results reflect the necessity of evaluating cautiously the data obtained in demographic studies by different sampling protocol.